1936
DOI: 10.1042/bj0300558
|View full text |Cite
|
Sign up to set email alerts
|

The assay and the effect of testosterone on rats compared with those of other sexual hormones

Abstract: prepared this compound artificially. The natural and artificial preparations were similar in all respects, one capon unit being contained in about 10y and the effect on the seminal vesicles of castrated rats being greater than that on the prostate. According to Tschopp [1935; Ruzicka and Wettstein, 1935, p. 1270] 10y of testosterone injected into castrated rats for 10 days brought about an increase in the size of the seminal vesicles of about 300 % and of the prostate of about 113 %.. Laqueur et al. foumd that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1936
1936
1952
1952

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Oestrone and oestradiol belong to this group. These hormones do not cause any considerable return towards normal of the atrophied prostate, penis and male preputial glands (or eveti of the female preputial glands, which always respond to the hormones of the previous group), although they produce a definite increase in the weight of the seminal vesicles (with specific histological changes in the latter and also in the coagulating glands and prostate [Korenchevsky & Dennison, 1935]).…”
Section: Partially Bisexual Hormonesmentioning
confidence: 97%
“…Oestrone and oestradiol belong to this group. These hormones do not cause any considerable return towards normal of the atrophied prostate, penis and male preputial glands (or eveti of the female preputial glands, which always respond to the hormones of the previous group), although they produce a definite increase in the weight of the seminal vesicles (with specific histological changes in the latter and also in the coagulating glands and prostate [Korenchevsky & Dennison, 1935]).…”
Section: Partially Bisexual Hormonesmentioning
confidence: 97%
“…35, pp, 63-67. 1940 Implantation of hormonal substances in the anterior chamber of the eye of rats. Proc.…”
Section: Ijterature Citedmentioning
confidence: 99%
“…The biological and chemical position of trans-androstenediol between the male and the ovarian hormones has been emphasised by Tschopp [1935] and by Butenandt [1936]. Androstanediol and testosterone will also cause enlargement of the uterus of the adult ovariectomised rat [Korenchevsky, Dennison, and Simpson, 1935;Korenchevsky, Dennison, and Brovsin, 1936].…”
Section: Introductionmentioning
confidence: 99%
“…As regards the crystalline hormones, cestrone by itself will produce a pseudo-mucification of the epithelium [Robson, 1931], progesterone has no effect at all [Selye, Browne, and Collip, 1936 a], while the simultaneous administration of cestrone and progesterone will produce the full mucification which is found at the end of pregnancy [Selye, Browne, and Collip, 1936 b]. Korenchevsky and Dennison [1936] have shown that both androstanediol and testosterone can not only cause mucification of the vaginal epithelium directly, but also can modify-the action of cestrone when given in conjunction with it to produce complete mucification. In this respect, therefore, these two male hormone substances may be considered to have certain properties akin to those of progesterone but also others differing from them.…”
Section: Introductionmentioning
confidence: 99%